GC-MS ANALYSIS AND ANTIMICROBIAL ACTIVITY OF SYZYGIUM AROMATICUM EXTRACTS FROM TAIF, SAUDI ARABIA - HAYAM S. ABDELKADER,; EMAN M. HALAWANI, (International Journal of Pharma and Bio Sciences, 2014)
Antimicrobial activity of alcoholic and aqueous extracts from Syzygium aromaticum (clove) was evaluated against six Gram-negative bacteria, three Gram-positive bacteria and one fungus isolate. Clove extracts demonstrated broad spectrum antimicrobial activities against the tested microorganisms. Gram-positive bacteria were more sensitive than Gram-negative bacteria (MICs and MBCs of 62.5 to 250 μg/ml and 62.5 to 500 μg/ml) respectively. Interestingly, Psuedomonas aeruginosa 359 ETT which is resistant to most antibiotics was relatively more sensitive than other Gram-negative bacteria. While nhexane extracts showed very low activity against the test microorganisms, methanol extract was recorded as the most active extract against Pseudomonas aeruginosa ATCC 27853, E. coli ATCC25922, Staphylococcus aureus 375 at MBC of 62.5 μg/ml. Clove buds essential oils were characterized by GC/MS. Benzyl Alcohol (56.2362 %) and Eugenol (32.5%) were recorded as the major components in clove oil followed by β- Caryophyllene (8.97%) and Ocimene (1.126%). Therefore, the study shed the light on the efficacy of plant extracts to combat pathogens which will help as natural antimicrobial agents of sustainable eco-friendly botanical bactericides.